SALAM ATAU SELOMITA: TINJAUAN SASTRA DAN MASYARAKAT - Eva Farhah (Arabic Literature Department, 2017)
This research aims to find out the social phenomenon in short story untitled Salam aw Selomita (1983). These phenomena are seen as a personification of activities or facts related to the setting of society, particularly Palestine society in which the short story takes place. The short story consists the continuing conflict and permanent battle in Palestine society that can provide for the readers several valuable social phenomena. Hence the short story was intended one of conveying aspiration means for present society. This research uses the theory of the sociology of literature as a subfield viewing literary facts as a reflection of society, an empirical reality experienced by Palestine society, and uses the method by revealing events that experienced by Palestine society represented by actor Salam or Selomita, a reflection of social facts in current Palestine society. The research’s results show that the social phenomenon in the short story untitled Salam or Selomita is kidnapping the Palestinians children conducted by colonialist. The kidnapping has left a deep grief and tears for the parents and the Palestinians.